Research advances in huntingtin-associated protein 1 and its application prospects in diseases - Wu, Yongjiang; Wang, Yanfei; Lu, Yunchi; Yan, Junguo; Zhao, Hongjun; Yang, Riyun; Pan, Jingying (Frontiers in Neuroscience, 2024)
Huntingtin-associated protein 1 (HAP1) was the first protein discovered to interact with Huntingtin. Besides brain, HAP1 is also expressed in the spinal cord, DRG, endocrine and digestive systems. HAP1 has diverse functions involving in vesicular transport, receptor recycling, gene transcription and signal transduction. HAP1 is strongly linked to several neurological diseases, including Huntington's disease, Alzheimer's disease, epilepsy, ischemic stroke, and depression. In addition, HAP1 has been proved to participate in cancers and diabetes mellitus. This article provides an overview of HAP1 regarding the tissue distribution, cell localization, functions, and offers fresh perspectives to investigate its role in diseases.